2023
DOI: 10.1039/d3ob01416a
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic sulfur controlled efficient ketothioamide synthesis from tribromomethyl carbinols

Shubham Tiwari,
Sandeep Chandrashekharappa,
Guddeangadi N. Gururaja

Abstract: A greener approach towards diverse α-ketothioamides is demonstrated with a broad substrate scope. The presented protocol establishes the reactivity of the polysulfide derived from elemental sulfur and amines in an aqueous medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Our recent studies have shown that tribromomethyl carbinol (6) can be efficiently transformed into ketothioamide (7) (Scheme 5a). 20 Under established conditions, the substrates, such as tribromo-methylated adducts derived from activated alkene 21 (8), proceed to the corresponding thioamide formation (Scheme 5b). Further, thioamide (11) was formed from 2-nitro ethylbenzene 22 (10) under established reaction conditions (Scheme 5c).…”
mentioning
confidence: 99%
“…Our recent studies have shown that tribromomethyl carbinol (6) can be efficiently transformed into ketothioamide (7) (Scheme 5a). 20 Under established conditions, the substrates, such as tribromo-methylated adducts derived from activated alkene 21 (8), proceed to the corresponding thioamide formation (Scheme 5b). Further, thioamide (11) was formed from 2-nitro ethylbenzene 22 (10) under established reaction conditions (Scheme 5c).…”
mentioning
confidence: 99%